Classroom Management Talk in Teaching English at SMPN 2 Watampone - Mukhlis Mukhlis (ELT Worldwide: Journal of English Language Teaching, 2017)
This paper depicts the transactional expressions used by the teacher in teaching English, the students’ understanding of those transactional expression used, and the transactional expressions which gave benefit to the students. There were twenty two students and one English teacher involved as the subjects. The subjects were the students of the seventh grade of A of SMPN 2 Watampone and an English teacher who taught English in that class. This research employed a descriptive qualitative method by using a discourse analysis. The triangulation data were applied in this research. The researcher used observation sheet that entailed video recording to collect the data about the transactional expressions used by the teacher. To get deeper data about the transactional expressions used by the teacher, the researcher also employed interview instrument entailing audio recording. An open ended questionnaire was also distributed to the students to know about their understanding of the transactional expressions used by the teacher and the transactional expressions which gave benefit to them. The findings of this research revealed the real transactional expressions (management talk) used by the teacher in teaching English, the percentage of the students’ understanding of the transactional expressions used, and the beneficial transactional expressions for them.Key words: Classroom interaction, Management talk (transactional expressions), Students’ understanding, the beneficial transactional expressions, English Teacher, Students